Analysis of 30 patients with persistent or recurrent squamous cell carcinoma of the cervix within one year after concurrent chemoradiotherapy - Shi-Ping Liu; Jia-Xin Yang; Dong-Yan Cao; Keng Shen (Cancer Biology & Medicine, 2013)
Objective:To investigate the recurrence sites, risk factors, and prognosis of patients with persistent or recurrent squamous cell carcinoma (SCC) of the cervix within one year after undergoing concurrent chemoradiotherapy (CCRT). Methods:Clinical data of 30 patients with persistent or recurrent SCC of the cervix within one year after CCRT between July 2006 and July 2011 were analyzed retrospectively. These data were compared with those of 35 SCC cases with no signs of recurrence after complete remission. These 35 patients were treated during the same period (between 2006 and 2011) and selected randomly. Results:Among these 30 patients, 25 exhibited distant metastases of which 14 were observed within 6 months after CCRT. Univariate analysis showed higher incidence of pelvic or para-aortic lymphadenectasis and SCC-ag >10 ng/mL in the group with persistent or recurrent disease before treatment (P<0.01). Multivariate analysis by logistic regression revealed that the pre-therapeutic pelvic or para-aortic lymph node enlargement and SCC-ag >10 ng/mL were the independent risk factors. Palliative chemotherapy was the main treatment option for patients with persistent or recurrent disease. The 2-year survival rate was 21.7%, and the median survival time was 17 months. Conclusion:Patients with persistent or recurrent SCC of the cervix after CCRT exhibited a high rate of distant metastasis with poor prognosis. The pre-therapeutic pelvic or para-aortic lymph node enlargement and SCC-ag >10 ng/mL were identified as the independent risk factors for persistent or recurrent SCC within 1 year after CCRT.